Performance of the capacitive moisture sensor under different saline conditions - Pereira dos Santos, Clarissa (Revista Ciência Agronômica, 2021)
Capacitive methods for determining soil moisture are extremely practical and easily applied in the agriculturalenvironment, but are influenced by temperature, salinity and the type of soil. In this study, the aim was to verify the performanceof the Capacitive Moisture Sensor for Porous Media when subjected to saline media. The sensor under evaluation wasdeveloped at the Federal University of Ceará, and provides measurements and electrical frequencies related to soil moisture.The capacitive sensor for porous media was subjected to saline solutions with different concentrations of potassium chloride(KCl), when it was seen that the sensor electrodes appear sensitive to salinity when inserted in saline aqueous solutions withan electrical conductivity of up to 4 dS/m. Adjustments to the RC (resistor-capacitor) circuit were tested as an alternative tolessen the effect of salinity on the measurements, and it was possible to generate readings related to soil moisture in electricalfrequencies ranging from kHz to MHz. Tests were then carried out in a sandy soil under different conditions of moisture andsalinity. No significant differences were seen when using different resistors in the RC circuit that was constructed to lessen theeffects of salinity on the measurements taken by the sensor, whether in solution or in the soil.